Validity and reliability of the Persian version of the SARC-F questionnaire among Iranian older adults - Sanay Toloueinasab; Ahmad Delbari; Marjan Haghi; Vahid Rashedi; Zhale Zandieh (BMC Geriatrics)
Abstract Background Sarcopenia is recognized as a geriatric condition marked by a progressive decline in muscle mass and function. The SARC-F questionnaire was developed as a brief, self-reported, and cost-effective tool for screening sarcopenia. This study aims to translate and culturally adapt the SARC-F questionnaire into Persian and evaluate its psychometric properties for older adults attending outpatient geriatric clinics. Methods The study was conducted in two phases: translation and cultural adaptation, followed by psychometric evaluation. The Persian SARC-F was translated using the WHO forward-backward protocol and assessed for content validity using the Lawshe method. A cross-sectional study was conducted with 200 older adults aged 65 and above attending outpatient geriatric clinics in Tehran. Concurrent validity was assessed through a comparison of the Persian SARC-F with AWGS 2019 criteria for possible sarcopenia. Construct validity was assessed using the LEIPAD questionnaire, anticipating strong correlations with similar domains and weaker correlations with different domains. Internal consistency was determined using Cronbach’s alpha, and test-retest reliability was evaluated using the intraclass correlation coefficient (ICC). The diagnostic characteristics were determined by constructing a receiver operating characteristic (ROC) curve using the AWGS 2019 criteria for possible sarcopenia. Results The Persian SARC-F showed adequate content validity with S-CVI/Ave values of 0.97 for relevancy and clarity and 1 for simplicity. The CVR values for individual items ranged from 0.80 to 1. Concurrent validity was demonstrated with Spearman’s correlations of (r = -0.73) for hand grip strength and (r = -0.76) for gait speed. Construct validity was supported by convergent and divergent validity. The Cronbach’s alpha was 0.79, indicating good internal consistency. The ICC was 0.99, showing excellent test-retest reliability. The area under the curve (AUC) was 0.91 (95%CI: 0.86–0.95). Sensitivity, specificity, PPV, and NPV for the optimal cut point (≥ 4) were 84.9%, 96.5%, 96.9%, and 83.1%, respectively. Conclusions The Persian version of the SARC-F questionnaire is a valid and reliable tool with high diagnostic accuracy. It can be used for screening sarcopenia in Persian-speaking community-dwelling older adults.